Pemaknaan Hidup pada Wanita Single Parent Usia Dewasa Madya - Ai Hidayatunnajah (Jurnal Riset Agama, 2022)
Being a single parent is not easy, especially if it is experienced by a woman or mother who has reached middle adulthood. Where the age is no longer young, but the task is increasing. This study aims to find out what is the meaning of life, what is a single parent woman in middle adulthood, and how is the process of finding the meaning of life in single parent women in middle adulthood. The method used in this study is a qualitative method through a case study approach that produces descriptive data, namely written words or words from people or observed behavior. The meaning of life is a process to find the meaning of various events that have occurred both in the form of happiness and suffering and are reflected on oneself to achieve the goal, continue life until the individual feels a meaningful life and creates feelings of happiness. Everyone has the freedom to find the meaning of his life, so the meaning of life can be owned by anyone and under any conditions, one of which can be owned by a single parent woman in middle adulthood. The meaning of life is not found just like that, but is pursued through a process, one of which is through the spiritual dimension. Because the meaning of life is inseparable from the spiritual dimension, then one aspect of one's success in achieving the meaning of life is through the way of surrender, namely with Islam which is a work of outward practice and directed activity, faith which is inner worship and ihsan which is awareness in every person. steps taken, words spoken, and actions taken.